ELECTIONS, VIOLENCE AND TRANSITIONAL JUSTICE (Hekima Review, 2023)
In most African countries, election periods have often been associated with political tensions, electoral irregularities, rigging, voter bribery and sometimes violence. In most instances, these periods culminate in the announcement of controversial election results, which split the population, leading to violence. The degree of such situations in Africa varies in intensity from country to country, thus the need for transitional justice mechanisms to ensure accountability of individuals with the highest responsibility in perpetuating violence.